PENGARUH FINANCIAL DISTRESS DAN FIRM SIZE TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING : THE EFFECT OF FINANCIAL DISTRESS AND FIRM SIZE ON COMPANY VALUE WITH PROFITABILITY AS AN INTERVENING VARIABLE - Weni, Darma; Kamaliah, Kamaliah; Savitri, Enni (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2024)
Company has a goal of maximizing the value of the company, which aims to maximize shareholder prosperity. This study aims to analyze the factors that influence firm value. The variables used in this study are Financial Distress, Firm Size and Profitability. This research was conducted on property and real estate sector companies listed on the IDX in 2016-2020. Sampling was carried out using a purposive sampling method which resulted in 18 companies as research samples from a population of 48 companies. The research method used in this research is analysis of Partial Least Square (PLS). The results of the study show that financial distress has a negative and significant effect on profitability; firm size has a positive and significant effect on profitability; financial distress has no effect on firm value; firm size has no effect on firm value; profitability has a positive and significant effect on firm value; profitability can mediate the relationship between financial distress and firm value; profitability cannot mediate the relationship between firm size and firm value.